Time domain assessment of nonlinear coupled ship motions and sloshing in free surface tanks - Cercos Pita, Jose Luis; Souto Iglesias, Antonio; BULIAN, GABRIELE (Volume 1: Offshore Technology; Offshore Geotechnics, 2015)
Ships at sea almost invariably carry liquids onboard, and liquids are contained in appropriate tanks. Being able to take into account the effects of liquids onboard when predicting ship motions is, therefore, of utmost importance for the safe operation of a vessel. In certain conditions, such predictions also require taking into account nonlinearities in both ship motions and in the internal flow, and linear approaches are not sufficient. Within this context, the present paper describes a simulation approach where a blended 6-DOF nonlinear ship motions prediction solver handling the external fluid-ship interaction, is coupled with a Smoothed-Particle-Hydrodynamics (SPH) solver for simulating the internal flow tank dynamics. The solvers are described and an example application is reported.